Popular music and national culture in Israel - Regev, Motti (University of California Press, 2004)
A unique Israeli national culture--indeed, the very nature of "Israeliness"--Remains a matter of debate, a struggle to blend vying memories and backgrounds, ideologies and wills. Identifying popular music as an important site in this wider cultural endeavor, this book focuses on the three major popular music cultures that are proving instrumental in attempts to invent Israeliness: the invented folk song repertoire known as Shirei Eretz Israel; the contemporary, global-cosmopolitan Israeli rock; and the ethnic-oriental musica mizrahit